951 Recurrent Priapism Presenting with a Rare Cause in an Infant. (October 2012) - Warren, C; Fontaine, T; Bedwani, S
Abstract : Discitis in children is an important infective cause of morbidity and often has an insidious presentation, which creates difficulty in making a prompt diagnosis and instigating appropriate treatment. Priapism in the paediatric population is a rare urological emergency. It is most commonly associated with sickle cell disease and leukaemia, causing a vaso-occlusive priapism, and rarely with spinal shock. To the authors' knowledge, priapism secondary to discitis has not previously been described in the literature. We present a case of a 12 month old Caucasian child presenting with a three-week history of regular episodes of seemingly painful, persistent erections. He was noted to have a reluctance to sit or walk. Clinical examination was unremarkable other than priapic episodes. Neurological and haematological causes were considered but initial investigations were normal. An MRI of his spine, performed due to a later rise in erythrocyte sedimentation rate and a clinical deterioration with complete refusal to mobilise, demonstrated inflammatory changes at the L3/L4 level with a seven-millimetre collection, thus indicating discitis. He was treated with intravenous antibiotics and after ten days made a full recovery with complete resolution of his symptoms. This is the first reported case of discitis presenting as recurrent priapism in an infant. We feel that this case highlights the need to consider infective causes in children presenting with priapism, so that diagnosis and treatment of a significant underlying cause is not delayed. Early spinal imaging may be worthwhile in cases of unexplained priapism, particularly when haematological causes have been excluded.